SOCIAL MEDIA, YOUTH AND ENVIRONMENTAL LOW-RISK ACTIVISM: A CASE STUDY OF SAVESHARKS INDONESIA CAMPAIGN ON TWITTER - Hersinta Hersinta; Adithiyasanti Sofia (ASPIKOM Jabodetabek Region, 2020)
The lack of understanding and awareness on shark’s conservation in Indonesia is still largely found. Evidently, it could be seen from the massive reducing number of shark’s population, irresponsible consumption of shark meat, and constant activities on illegal, unregulated and unreported shark fishing and finning in Indonesia. On the other hand, shark existence is considered critical for sustainability in the marine area. In 2012, Savesharks Indonesia has started an online campaign on Twitter as their effort to raise public awareness of the critical role of sharks’ conservation. However, social media activism has the possibility to lead into ‘slacktivism’, or ‘feel good’ activism; without creating a meaningful impact for the cause. This article is intended to explore the relationship between online environmental activism and its implication toward the cause. On the first stage, we analyse the Twitter content in 2014 Savesharks campaign – based on Lovejoy & Saxton (2012) framework of communicative functions in Twitter environmental advocacy. On the second stage, we conduct interviews with informants who represent Savesharks’ campaign audience – to investigate the level of activism that the audience refers to in this campaign. Results indicate that Savesharks Indonesia online activism has reached the action stage where the audience were involved not only in online realm of activism but also in offline forms. However, the online activism of Savesharks Indonesia was reflecting more of a “populist political activism” (Lim, 2013). As such, it is still questionable whether the activism could lead to tangible political actions (e.g. influencing the environmental policies).